Tiempo débil: La trascendencia de los géneros (2021)
This project addresses a process of research creation about the leading factor within the elements present in the weak times that have been transcendental in the pieces and musical forms in the essential genres from the 60's to the present, which have served to redefine their styles and sounds as breaking points in a musical timeline in the context of mass reach. Under this research premise, it seeks to design from the axis of musical pre-production, production, post-production, a sound result of sound exploration in digital format through an imperative remote work, which redefines current pop music with the use of these innovative elements, thus marking the evolution of the genre supported by 1 EP of 3 songs by 3 different international and national artists.